Optimization of Benzene and Toluene Biodegradation by Aspergillus niger and Phanerochaete chrysosporium - Analekta Tiara Perdana; Mutia Arianata; Tri Retno Dyah Larasati (Universitas Al Azhar Indonesia, 2019)
Abstract - Benzene and toluene can cause contamination in environments. Utilization of microorganism to degrade these compounds could be favorable approach to discover a convenient biodegradation agent. Fungi have an important role in the degradation of petroleum hydrocarbon (PHC). The aim of this study was to evaluate the potential of benzene and toluene degrading molds Aspergillus niger and Phanerochaete chrysosporium. These molds were selected to check the Lignin Peroxidase (LiPs) activity and formulate the medium conditions for improving degradation process. Optimization of medium conditions (pH and nutrient concentrations) for benzene and toluene degradation was applied under in vitro conditions. Molds were grown in sawdust media with pH settings (4, 5, 6 and 7) and nutrients (25%, 50%, 75% and 100%) followed by the addition of benzene and toluene. The percentage of degradation was analyzed using Gas Chromatography (GC). The optimal degradation conditions of benzene and toluene by A. niger were at pH 6 with nutrient concentration of 75%, while P. chrysosporium at pH 7 with nutrient concentration of 25%. All samples that had been polluted by benzene and toluene did not show LiPs activity, however non polluted samples showed LiPs activity 0,528 U/ml in A. niger and 0,275 U/mL in P. chrysosporium.Keywords- Aspergillus niger, Benzene, Biodegradation, Phanerochaete chrysosporium, Toluene.